Rancang Bangun Realtime Sounding pada Storage Tank Simulator Berbasis Mikrokontroler AVR ATMEGA 8535 - Ahmad Mahfud (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
This research discusses the design of a sounding system that measures the liquid content in a simulation tank, which is a model of a palm oil storage tank. With a heating treatment by the heater to effect temperature changes and the installation of a solenoide valve to give effect to changes in fluid height. The use of ultrasonic sensors (HC-SR04) can be used to test the height level of empty space with a level of accuracy of 1 cm. The use of a temperature sensor (DS18B20) can be effectively used to measure temperature with a small dipped method in liquid. ATMEGA 8538 AVR microcontroller, is able to communicate well with applications built on the Borland Delphi platform, so as to provide comfort and convenience for users to monitor and read the performance of tank contents, both from the level, temperature, density, and tank contents in the form of number and graphic.